2002
DOI: 10.1002/dev.10059
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic methylphenidate administration has no effect on locomotion, emotional behavior, or water maze learning in prepubertal mice

Abstract: Methylphenidate hydrochloride (Ritalin, MPH) is frequently prescribed as a treatment for children with attention deficit hyperactivity disorder (ADHD), yet little research has been conducted to determine its potential long-term neurobehavioral effects. We assessed the effects of subchronic MPH administration (2.5, 5, 10, 20, 40, or 80 mg/kg) on male CD-1 mice treated from 26 to 32 days of age. When tested at 33 days of age in the open field and elevated plus maze, there were no significant differences in spont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…These results are consistent with Zubrycki et al [29], Broderick et al [30] and Damianopoulos and Carey [31], who showed increased locomotion in an open field test following cocaine administration compared to saline-treated rats. McFadyen et al [32], and Ferguson and Cada [33] exhibited similar results to ours, showing no methylphenidate effect on open field performance. On the contrary, Yang et al [34] showed increased locomotion 20 min after methylphenidate administration.…”
Section: Open Field Testsupporting
confidence: 90%
“…These results are consistent with Zubrycki et al [29], Broderick et al [30] and Damianopoulos and Carey [31], who showed increased locomotion in an open field test following cocaine administration compared to saline-treated rats. McFadyen et al [32], and Ferguson and Cada [33] exhibited similar results to ours, showing no methylphenidate effect on open field performance. On the contrary, Yang et al [34] showed increased locomotion 20 min after methylphenidate administration.…”
Section: Open Field Testsupporting
confidence: 90%
“…Some studies show decreases (McFadyen-Leussis et al, 2004), and others show increases (Carrey et al, 2000;McFadyen et al, 2002;Bolanos et al, 2003) in anxiety-like behaviors after MPH administration. In the present study, two tests were performed to assess anxiety levels in the male PND135 rats, which received MPH or saline from PND7-PND35 and then were drug-free for 3 months.…”
Section: Developmental Mph Administration Can Influence Behavior Durimentioning
confidence: 99%
“…For example, juvenile exposure to MPH produces an aversion to cocaine-associated environments in adulthood [7, 8], whereas exposure during adolescence [9] or adulthood [10] increases self-administration of cocaine. Other studies report no significant behavioral effect [11]. …”
Section: Introductionmentioning
confidence: 99%